2017
DOI: 10.4172/1747-0862.1000287
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil for Lewy Body Constipation: A Six-Month Follow-up

Abstract: In a previous case study, four patients at different stages of Parkinson's disease (PD) and Neurocognitive Disorder with Lewy Bodies (NCDLB) disease progression were treated with Donepezil, with the intention of mitigating Lewy body impairment of the cholinergic pathways in the myenteric plexus, increasing bowel motility, and reducing the symptom of constipation. In all four cases, the use of Donepezil was associated with significant reduction of the symptom of constipation. There was no exacerbation or instig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A follow up study indicated that the progression of Lewy body pathology had advanced in some patients, leading to exacerbation of CNS and ANS symptoms including blunted affect, dysphoric mood, generalized anxiety, sleep disturbance (onset, median and terminal waking, REM sleep behavior disorder or RSBD and/or REM sleep without atonia, or RSWA), cognitive interference (short-term memory loss and difficulty with wordfinding), passive suicidal ideation, appetite suppression, and exacerbation of Parkinsonian features (motor retardation, joint and muscle pain, reduced range of motion, diminished strength and coordination, increased tremor, gait disturbances, and difficulties with balance). However, there was no exacerbation of the symptom of constipation, nor emergence of new symptoms in any of the patients in the study, suggesting that Donepezil might have long-term benefit for mitigating cholinergic Lewy pathology in the ENS of patients with PD and NCDLB [40].…”
Section: Symptom Treatment Of Cholinergic Lewy Pathology In the Ensmentioning
confidence: 79%
See 4 more Smart Citations
“…A follow up study indicated that the progression of Lewy body pathology had advanced in some patients, leading to exacerbation of CNS and ANS symptoms including blunted affect, dysphoric mood, generalized anxiety, sleep disturbance (onset, median and terminal waking, REM sleep behavior disorder or RSBD and/or REM sleep without atonia, or RSWA), cognitive interference (short-term memory loss and difficulty with wordfinding), passive suicidal ideation, appetite suppression, and exacerbation of Parkinsonian features (motor retardation, joint and muscle pain, reduced range of motion, diminished strength and coordination, increased tremor, gait disturbances, and difficulties with balance). However, there was no exacerbation of the symptom of constipation, nor emergence of new symptoms in any of the patients in the study, suggesting that Donepezil might have long-term benefit for mitigating cholinergic Lewy pathology in the ENS of patients with PD and NCDLB [40].…”
Section: Symptom Treatment Of Cholinergic Lewy Pathology In the Ensmentioning
confidence: 79%
“…Donepezil has demonstrated efficacy in mitigating Lewy body impairment of the cholinergic pathways in the MP and CSMP of patients diagnosed with PD and NCDLB, increasing bowel motility and reducing the symptom of constipation, without exacerbating or instigating other symptoms [39,40]. One possible conclusion is that the use of the AChEI Donepezil compensates at least in part for Lewy body impairment of cholinergic pathways in the MP and CSMP, reducing the symptom of constipation in patients with PD and NCDLB.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations